Determinants of contractual relations between shareholders and bondholders: investment opportunities and restrictive covenants - Nash, Robert C; Netter, Jeffry M; Poulsen, Annette B (Journal of Corporate Finance, 2003)
We evaluate the costs and benefits of restrictive covenants in bonds issued in 1989 and 1996. Our results indicate that firms with growth opportunities are more likely to seek to preserve flexibility in future financing activities by not including dividend or debt issuance restrictions in their bond contracts. We do not find, however, that the use of other restrictive covenants is significantly lower for firms with high investment opportunities. Instead, the use of these other covenants is primarily driven by the issuing firm's likelihood of financial distress. Our results emphasize that contractual relations between firms and bondholders reflect the specific needs of the contracting parties.